Spontaneous Remission of Pediatric Undescended Testis Torsion during Color Doppler Ultrasound Examination - Huiyong Hu, MS, Hairong Wang, MS, Yunfeng Xu, MS (Advanced Ultrasound in Diagnosis and Therapy, 2023)
Undescended testis or cryptorchidism is the most common reproductive system disease in children. About 3% of full-term and 30% of premature male infants are born with one or both testicles undescended. Most cryptorchidism is asymptomatic and is occasionally found due to inguinal pain caused by testicular torsion. Herein, we presented a case of pediatric patient with abdominal pain as initial symptom who was found the left inguinal cryptorchidism complicated by testicular torsion, and then spontaneous remission during the color Doppler ultrasonography examination.